Current Treatment Options for Intervertebral Disc Pathologies. (April 2020) - Eisenstein, Stephen M.; Balain, Birender; Roberts, Sally
The complex structure of the intervertebral disc within the spine is well suited to its mechanical function. However, it is also prone to degeneration, which is associated with various clinical symptoms and conditions, ranging from disc herniation to back pain to spinal stenosis. Most patients' conditions are managed conservatively but a small proportion progress to having surgery. This may be decompression (to remove tissue such as the disc, bone, or hypertrophic ligaments impinging on nerves) or fusion of the normally mobile intervertebral joint to immobilize it and so reduce pain. These used to involve fairly major surgical procedures, but in the past decade there has been much progress to make the surgery more refined and less invasive, for example using endoscopic approaches. Simultaneously, the research world has been studying and developing tissue engineering and cellular techniques for attempting to regenerate the intervertebral disc, whether simply the central nucleus pulposus or a complete intricate assembly to replicate the native structure of this and the surrounding annulus fibrosus, cartilage endplate, and bone. To date, none of the complex entities have been trialed, while cellular approaches are easier to utilize, have progressed to clinical trials, and may offer a better solution.